The Mechanism of Human Connectedness in Relationship to Physical Health, Mental Health, and Cognitive Function Among the Elderly in Rural China - Xu, Shicun; Wang, Yuanyuan; Yu, Hui (Frontiers in Psychiatry, 2021)
Background: The elderly face particular challenges in everyday life, including declined physical and mental health, cognitive function, as well as greater difficulty in maintaining a satisfactory human connectedness. This study aimed to explore a meaningful measure of human connectedness among elderly in rural China, also to examine the importance of connectedness in relationship to the elderly’s physical and mental health, as well as their cognitive function. Methods: Survey data were collected from 483 participants who aged 60 and above in Northeast rural China. The Short Portable Mental Status Questionnaire was used to assess participants’ cognitive function; depression was measured by 10-item version of Center for Epidemiologic Studies Depression Scale; the perceived family support was measured by Multidimensional Scale of Perceived Social Support; the community feeling was measured by the Brief Sense of Community Scale. We also measured the Satisfaction of the connectedness with others (family members, friends and children and grandchildren), and physical illness. Results: Structural Equation Modelling (SEM) analysis has confirmed that the perceived family support, community feelings, and the perceived satisfaction of family and friend connectedness comprised of a good structure in capturing human connectedness, and the connectedness significantly predicted one’s mental and physical health, as well as their cognitive function. Discussion: The present study is the first attempts to explore the latent structure of human connectedness and its positive impact on cognitive function as well as physical and mental health among elderly people. The implications and the importance of fostering a stronger social support network especially for the aging population are discussed.